EVALUASI KINERJA ASET FASILITAS REKREASI DI TERAS CIKAPUNDUNG KOTA BANDUNG - Karina Aurora Nadea (Pondasi, 2021)
ABSTRACTOne of the city parks designed as a recreation area is Teras Cikapundung. Teras Cikapundung has an area of 5,128 m2 and located in the Siliwangi area of Bandung City. Based on the results of preliminary observations have found several indications of problems with existing facilities in the Teras Cikapundung recreation area, namely non-operational children's rides, unavailability of parking spaces for bicycles, the stairs are not equipped with handrails, some of park chairs, picnic tables, and garden lights can’t be used because in the damage condition, and there is only two kind of signage: direction and information. The purpose of this case study research is to determine the performance of facility assets based Recreational Facility Audit Tool and provide solutions or recommendations for problems in recreational facilities in Teras Cikapundung. The theory for this research based on 'The Recreational Facility Audit Tool' from Macfarlane et al (2013) includes availability of sport facilities, accessibility, and availability of supportive amenities. The research method is descriptive method with qualitative and quantitative research approaches. The data collection techniques were observation, interview, and documentation study. The analysis techniques is using descriptive analysis techniques. Therefore, the recommended problem solving recommendation is the renovation of recreational facilities assets in Teras Cikapundung Bandung City.Keywords: Asset Performance Evaluation, City Park, Recreational FacilitiesABSTRAKSalah satu taman kota yang dirancang sebagai tempat rekreasi taman kota adalah Teras Cikapundung. Teras Cikapundung memiliki luas sebesar 5.128 m2 dan berlokasi di daerah Siliwangi Kota Bandung. Berdasarkan hasil observasi pendahuluan ditemukan beberapa indikasi masalah pada fasilitas yang ada pada kawasan rekreasi Teras Cikapundung yaitu permainan anak yang tidak beroperasi, tidak tersedianya tempat parkir untuk sepeda, tangga yang disediakan tidak dilengkapi oleh pegangan, selain itu beberapa fasilitas kursi taman, meja piknik, dan lampu taman tidak dapat digunakan karena dalam kondisi rusak, serta hanya tersedia 2 jenis rambu yaitu rambu petunjuk arah dan informasi. Tujuan penelitian studi kasus ini untuk mengetahui kinerja aset fasilitas berdasarkan Recreational Facility Audit Tool dan memberikan solusi atau rekomendasi atas permasalahan yang terdapat pada fasilitas rekreasi di Teras Cikapundung. Teori yang digunakan pada penelitian ini adalah ‘The Recreational Facility Audit Tool’ dari Macfarlane et al (2013) meliputi availability of sport facilities, accessibility, dan availability of supportive amenities. Metode penelitian yang digunakan adalah metode deskriptif dengan pendekatan penelitian kualitatif dan kuantitatif. Teknik pengumpulan data yang digunakan yaitu observasi, wawancara, dan studi dokumentasi. Teknik analisis yang digunakan adalah teknik analisis deskriptif. Rekomendasi pemecahan masalah yang disarankan dalam penelitian ini adalah renovasi aset fasilitas rekreasi di Teras Cikapundung Kota Bandung.Kata kunci : Evaluasi Kinerja Aset, Fasilitas Rekreasi, Taman Kota